Transforming lives: Peace David's journey with farmers outreach - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In this video, Peace David shared how outdated techniques led to huge losses while he struggled to maintain a sustainable plantain farm. However, everything changed when he learned about certified planting materials, sucker management, and pest control from Radio IITA training